Effects of functional training on skill performance and movement quality among skilled youth male tennis players: A cluster randomized control trial - Wensheng, Xiao; Te, Bu; Feida, Zhao; Zhang, Junlong; Bai, Xiaorong; Soh, Kim Geok (BioMed Central, 2025)
Purpose: Functional training to improve athletes’ technical performance and movement quality is becoming increasingly popular, but few studies have focused on young tennis players. The aims of this study were to compare the effects of 12 weeks of functional training on skilled youth male tennis players’ skill performance and movement quality. Methods: Forty skilled youth male tennis players were assigned to the functional training group (n = 20) or the control training group (n = 20). The control group received a traditional resistance training program by their coach, whereas the functional training group was given Santana’s Racket Sports Program. Each group received 60-minute training sessions three times per week for 12 weeks. At baseline (T0), after six weeks (T6), and after 12 weeks (T12), the participants’ skill performance was measured according to the International Tennis Federation’s protocol, and movement quality was measured according to the functional movement screening assessment recommended by Gray Cook. The data were analyzed via a generalized estimation equation model. Results: The results revealed that there were no significant differences in skill performance or movement quality between the groups at baseline (p > 0.05), but there were significant differences in those variables between the groups after 6 weeks of the intervention and 12 weeks of the intervention (p < 0.05). Conclusion: These results indicate that the functional training model seems to be more effective than the traditional resistance training model in terms of increasing athletic skill performance and movement quality. The inclusion of functional training as part of an athlete’s training routine is highly recommended, as it has proven to be an effective method for improving skill performance and movement quality. Trial Registration: ISRCTN67565717, registered 26/07/2024, retrospectively registered. © The Author(s) 2025.